CHARACTERISTIC OF LABOR FUNCTIONS OF MANAGEMENT PERSONNEL OF EDUCATIONAL ORGANIZATION - V. Tarasenko (Вестник университета)
The article presents the results of the study of the management of the national education system. The author of the study claries the linear-functional model of educational organization management, consisting of the target subsystem (management of the development and implementation of the development strategy of the organization), linear subsystem (management of the educational process) and functional subsystems (personnel and resources management, management of social development processes). In accordance with the linear-functional model, the composition of specic functions of educational organization management is determined. On the basis of the matrix of specic functions of management of educational organization and invariant management functions (planning, organization, motivation, control) the modern list of labor functions of the management personnel of educational organization is substantiated.